1970
DOI: 10.7307/ptt.v24i1.269
|View full text |Cite
|
Sign up to set email alerts
|

DEA Window Analysis for Measuring Port Efficiencies in Serbia

Abstract: The aim of the paper is to apply Data Envelopment Analysis (DEA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…The model is based on the assumption that what was viable in the past remains viable forever, and that the treatment of time in windows analysis is more in the nature of an averaging over the periods of time covered by the window[20]. An important advantage of window analysis is that its increases the number of units for evaluation and in effect the discriminatory power of the method[21]. In applying window analysis, DEA first evaluates the performance of all DMU's in the same window and the efficiency of each DMU will be entered into the right window position in the table.…”
mentioning
confidence: 99%
“…The model is based on the assumption that what was viable in the past remains viable forever, and that the treatment of time in windows analysis is more in the nature of an averaging over the periods of time covered by the window[20]. An important advantage of window analysis is that its increases the number of units for evaluation and in effect the discriminatory power of the method[21]. In applying window analysis, DEA first evaluates the performance of all DMU's in the same window and the efficiency of each DMU will be entered into the right window position in the table.…”
mentioning
confidence: 99%
“…The model is based on the assumption that what was viable in the past remains viable forever, and that the treatment of time in windows analysis is more in the nature of an averaging over the periods of time covered by the window [31]. An important advantage of window analysis is that its increases the number of units for evaluation and in effect the discriminatory power of the method [32]. In applying window analysis, DEA first evaluates the performance of all DMU's in the same window and the efficiency of each DMU will be entered into the right window position in the table.…”
Section: Methodsmentioning
confidence: 99%
“…According to the empirical analysis, it was found that Japan is the most efficient country at the average efficiency level. Pjevčević et al (2012) measured the activities of the 5 harbors on the Danube River in Serbia. For this purpose, the 2001-2008 period dataset was analyzed.…”
Section: Introductionmentioning
confidence: 99%